Mathematical simulation of the reactor for the ethylbenzene to styrene dehydrogenation reaction. Issue 5 (November 2020) - Solovev, S A; Soloveva, O V; Gilmurahmanov, B Sh; Lamberov, A A
Abstract: In this work, we carried out a numerical simulation of an industrial reactor of a radial type with a fixed catalyst bed for the process of ethylbenzene to styrene dehydrogenation. We solved the problem in the approximation of two-dimensional axial symmetry. The parameters of the chemically reacting gas mixture movement in the catalyst bed are considered. The reactor zones which have a negative impact on the reaction efficiency have been determined.